High-grade adenocarcinoma, (ductal type) arising in unilateral Warthin tumor of the parotid gland - Kedar K Deodhar; Milap Shah; Pankaj Chaturvedi (Wolters Kluwer Medknow Publications, 2011)
Warthin tumor is a well-recognized benign salivary gland neoplasm consisting of an epithelial as well as a lymphoid component. Malignant transformation in Warthin tumor is rare and its reported incidence is up to 1%. The more common types of carcinomas described in Warthin tumor are the squamous and mucoepidermoid types, with high-grade adenocarcinoma being extremely rare. A high-grade adenocarcinoma (ductal type) arising in the Warthin tumor in a 72-year-old man is presented for its rarity and diagnostic difficulties.